2019
DOI: 10.1186/s12931-019-1094-y
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer development and mortality in interstitial lung disease with and without connective tissue diseases: a five-year Nationwide population-based study

Abstract: Background Connective tissue disease associated with interstitial lung disease (CTD-ILD) and interstitial lung disease (ILD) alone have same pathological and imaging backgrounds. However, the differences between lung cancer development and the mortality risk between these two conditions are unclear. Incidence of primary lung cancer and all-cause mortality were studied between interstitial lung disease patients with and without connective tissue disease. Methods Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…The incidence densities of LC in patients with CTD-ILDs were also reported in two previous studies as 0.98 and 1.66 per 100 person-years [14,15]. Thus, the incidence density of LC in CTD-ILD patients in this study was slightly lower than the values in previous reports [14,15]. Moreover, Choi et al reported that the incidence densities of LC in IPF and IIP patients were 3.81 and 1.57 per 100 person-years, respectively, and that the incidence of LC in IPF patients was higher than that in IIP patients based on data from the Korean national database [13].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The incidence densities of LC in patients with CTD-ILDs were also reported in two previous studies as 0.98 and 1.66 per 100 person-years [14,15]. Thus, the incidence density of LC in CTD-ILD patients in this study was slightly lower than the values in previous reports [14,15]. Moreover, Choi et al reported that the incidence densities of LC in IPF and IIP patients were 3.81 and 1.57 per 100 person-years, respectively, and that the incidence of LC in IPF patients was higher than that in IIP patients based on data from the Korean national database [13].…”
Section: Discussionsupporting
confidence: 70%
“…The incidence rate in this study was comparable with those in previous reports on IPF patients. The incidence densities of LC in patients with CTD-ILDs were also reported in two previous studies as 0.98 and 1.66 per 100 person-years [14,15]. Thus, the incidence density of LC in CTD-ILD patients in this study was slightly lower than the values in previous reports [14,15].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Patients who were less than 60 years old with connective tissue disease-associated ILD (CTD-ILD) were more likely to have concurrent malignancies than CTD-only patients. [ 45 ] However, studies on the association between ILD and malignancy in DM patients have shown that the presence of a malignancy occurs less frequently in the DM-ILD group than in the non-DM-ILD group. [ 2 , 12 , 29 , 34 ] In our cohort, 77.84% of DM patients had ILD.…”
Section: Discussionmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) is a primary class of lung cancer and ~85% of lung cancer cases are classified as NSCLC (3,4). Although great advancements have made in the clinic, the prognosis of NSCLC remains poor and the 5 year survival rate of patients from Europe with NSCLC remained at <15% in 2016, which may be due to the limitations of early detection methods (5)(6)(7). Thus, numerous recent studies have focused on investigating the molecular mechanisms associated with NSCLC progression in order to identify novel treatment methods (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%